Evidence of post-glacial secondary contact and subsequent anthropogenic influence on the genetic composition of Fennoscandian moose (Alces alces) - Kangas, Veli-Matti; Kvist, Laura; Kholodova, Marina; Nygren, Tuire; Danilov, Pjotr; Panchenko, Danila; Fraimout, Antoine; Aspi, Jouni (Blackwell, 2015)
AimTo determine whether a contemporary population of the moose (Alces alces), a large northern ungulate, retains genetic signatures of post-glacial recolonization and/or the effects of anthropogenic factors. We focused on investigating spatial genetic structure and the distribution of genetic diversity of this species to clarify its still obscure history. LocationEastern Fennoscandia, Northern Europe. MethodsIn total, 574 Finnish and Russian Karelian moose were genotyped at 16 microsatellite loci, and the mitochondrial control region was sequenced from 224 individuals. Spatially explicit Bayesian clustering, multivariate and spatial autocorrelation methods were applied alongside traditional F-statistics to study the effects of landscape on genetic structure. The demographic history of our study populations was explored with coalescent analysis and Bayesian skyline plots. ResultsA major mitochondrial divergence of moose was discovered between northern parts of Finland and the rest of the studied area. Landscape genetic analyses on the microsatellite data identified three genetic clusters connected by clines, with coalescent analysis indicating the division to be of ancient origin. Additionally, recent population bottlenecks were detected using Bayesian skyline plots. Main conclusionsOur results indicate a post-glacial secondary contact between two distinct moose mitochondrial lineages that diverged during the Pleistocene, whereas admixture of three diverged genetic subpopulations was detected using microsatellites. The emergence of these subpopulations was estimated to have occurred after the post-glacial recolonization of Fennoscandia. The observed genetic bottlenecks coincide with recorded historical population declines in the 18th century. We conclude that the contemporary genetic composition of the moose population in eastern Fennoscandia has been affected by both ancient and recent factors.
Keywords: Alces alces; genetic diversity; genetic structure; microsatellites; mitochondrial DNA; Northern Europe; post-glacial recolonization; secondary contact